World neglected tropical diseases day. - Peter J Hotez; Serap Aksoy; Paul J Brindley; Shaden Kamhawi (Public Library of Science (PLoS), 2020)
January 30, 2020 is the first-ever World Neglected Tropical Diseases Day (World NTD Day), a day when we celebrate the achievements made towards control of the world's NTDs, yet recognize the daunting challenges we face in the control and elimination of these conditions.